Processing of Liquid Confectionery Wastewater Using Combination of Electrocoagulation With UV Lights Method - Pradina, Sisca Chandra; Sutanto, Sutanto; Nuraeni, Farida (Universitas Pakuan, 2023)
Liquid confectionery waste water treatment is carried out using a combination of batch system electrocoagulation methods and irradiation by UV light. The variations of contat time applied were 30, 45, 60, and 75 minutes, the electrode distance was 2 cm and voltage variation was 20 and 30 volts. In addition to reducing pollutant levels, UV lamps are also used to remove odors. The result showed that the electrocoagulation process and UV irradiation could reduce pollutant levels maximally at 30 volts 73 minutes. COD level decreased to 1646,40 mg/L (efficiency 76,34%) and TSS to 50 mg/L (efficiency 88,68%). UV irradiation is also effective in removing the odor of soft confectionery wastewater. This result meets the wastewater quality stabdard according to PerMenLH No. 5 of 2015 Appendix XXVI, it’s just that COD does not meet the quality standards, therefore further research is needed.